PENGARUH PERMAINAN KEPALA BERANJAU TERHADAP PENINGKATAN PASSING BAWAH BOLA VOLI PADA SISWA PUTRA KELAS VIII SMP NEGERI 5 KOTA JAMBI: Eksperimen - Agus Parman; Ugi Nugraha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
There are many forms of game practice that can improve down-passing abilities, one of which is the open-head game, which can be used as a form of training for students in an effort to improve down-passing ability in volleyball games. The goal to be achieved through this research is to reveal the influence of the long-head game on improvement. Volleyball Bottom Passing in Class VIII Male Students of SMP Negeri 5 Jambi City. The research method used was an experimental method with a One Group Pre test - Post test design research design, with a sample size of 25 students from the existing population. The sample was obtained using a conditional sampling technique (Purposive Sample). This research began with an initial test and a final test for volleyball underpasses. The training was carried out for six weeks with a frequency of three times a week. The results of this study used quasi-experimental t-test data analysis which showed that there was an influence of the head-to-head game on improving volleyball bottom passing in class VIII male students at SMP Negeri 5 Jambi City (tcount 15.522 > ttable 1.711 with a confidence level of 95% ). Thus, Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of the head game on improving volleyball bottom passing in class VIII male students at SMP Negeri 5 Jambi City.